Social disadvantage, insufficient sleep, and cardiovascular disease - Kennedy, Gerard Anthony (Frontiers in Sleep, 2025)
The aim of this paper was to search the literature examining the relationships between social disadvantage, insufficient sleep, and cardiovascular disease and conduct a brief narrative review. A sleep disparity exists in the population with poor sleep quality strongly associated with poverty. Factors such as ethnicity, annual income, education, employment, and health status significantly mediate the effect in poorer disadvantaged people. In turn, the findings from large epidemiological studies show that insufficient sleep and/or insomnia, and/or short duration sleep are linked to increased risk of cardiovascular diseases such as hypertension, coronary heart disease, heart failure, stroke, arrhythmia, and cardiovascular mortality. In addition, insomnia together with objectively assessed short sleep duration confers a higher risk of developing cardiovascular diseases. However, more large epidemiological studies controlling for obstructive sleep apnoea are needed to fully confirm these findings.